Peran Tradisi Nyadran Dalam Memperkokoh Kerukunan Antar Masyarakat Desa Kalipucung - Mohamad Irfan Fatoni (Purwadita : Jurnal Agama dan Budaya, 2022)
Culture is a way of life and beliefs that can be accepted by a group of people. We must protect and preserve culture. One of them is this nyadran tradition. Nyadran is a series of activities or ceremonies aimed at praying for ancestral spirits which is carried out before Ramadan, namely in the month of Ruwah. In Kalipucung Village, the Nyadran tradition has positive values, impacts, and local wisdom for the community. So do not be surprised if this nyadran tradition in Kalipucung Village is still maintained and is still carried out regularly once a year. This study uses qualitative research methods and uses data collection of observations, interviews, and documentation. In addition, this study has the objectives of 1) describing the nyadran tradition, 2) describing the role of the nyadran tradition in strengthening harmony among the people of Kalipucung village.